Convergence to market efficiency of top gainers - Su, Yong-Chern; Huang, Han-Ching; Hsu, Ming-Wei (Journal of Banking & Finance, 2010)
This study investigates the convergence process toward efficiency of daily top gainers. The convergence process toward efficiency is much clearer as a result of using a GARCH(1,1) model compared to the OLS model, and exhibits a monotonic decline as the time interval increases. The relationship between volatility and order imbalances is, however, not strong enough, suggesting that market makers do have the capability to reduce price volatility. This study develops an imbalance-based trading strategy, which earns a positive profit but fails to outperform the buy-and-hold strategy (i.e., open-to-close returns). A nested causality approach, which examines the dynamic return–order imbalance relationship during the price-formation process, confirms the results.